Children and youth during the Gilded Age and Progressive Era - Marten, James Alan (Children and youth in America., 2014)
"In the decades after the Civil War, urbanization, industrialization, and immigration marked the start of the Gilded Age, a period of rapid economic growth but also social upheaval. Reformers responded to the social and economic chaos with a "search for order," as famously described by historian Robert Wiebe. Most reformers agreed that one of the nation's top priorities should be its children and youth, who, they believed, suffered more from the disorder plaguing the rapidly growing nation than any other group. Children and Youth during the Gilded Age and Progressive Era explores both nineteenth century conditions that led Progressives to their search for order and some of the solutions applied to children and youth in the context of that search. Edited by renowned scholar of children's history James Marten, the collection of eleven essays offers case studies relevant to educational reform, child labor laws, underage marriage, and recreation for children, among others. Including important primary documents produced by children themselves, the essays in this volume foreground the role that youth played in exerting agency over their own lives and in contesting the policies that sought to protect and control them"--